Diagnosis of severe dengue: Challenges, needs and opportunities - Wong, Pooi Fong; Wong, Li Ping; AbuBakar, Sazaly (Elsevier, 2020)
Background: Delayed diagnosis of dengue cases with increased risk for severe disease could lead to poor disease outcome. To date there is no specific laboratory diagnostic test for severe dengue. This qualitative study explored expert views regarding current issues in diagnosing severe dengue, rationale for severe dengue-specific diagnostics, future prospects and features of potential diagnostics for severe dengue. Methods: In-depth individual interviews with thematic saturation were conducted between May and July 2018. The data was analyzed using thematic analysis. Results: Based on expert opinion, diagnosis of severe dengue is challenging as it depends on astute clinical interpretation of non-dengue-specific clinical and laboratory findings. A specific test that detects impending manifestation of severe dengue could 1) overcome failure in identifying severe disease for referral or admission, 2) facilitate timely and appropriate management of plasma leakage and bleeding, 3) overcome the lack of clinical expertise and laboratory diagnosis in rural health settings. The most important feature of any diagnostics for severe dengue is the point-of-care (POC) format where it can be performed at or near the bedside. Conclusion: The development of diagnostics to detect impending severe dengue is warranted to reduce the morbidity and mortality rates of dengue infection and it should be prioritized. © 2020 The Authors